And Then There Was One: Moving and Merging Three Health Science Library Collections. - Mary Hitchcock; Rhonda Sager; Julie Schneider (Issues in Science and Technology Librarianship)
The article describes how the collections of the Middleton Health Sciences Library, the Powers Pharmacy Library and the Weston Clinical Sciences Center Library were merged and moved into the Health Sciences Learning Center as the Ebling Library at the University of Wisconsin-Madison. The planning and collection assessment conducted are discussed. Efforts to prepare the collection for the move and merge that were centered on the journal collections of the three libraries are highlighted.